Analisis Indeks Kerentanan Seismik di Desa Kalongan, Kecamatan Ungaran Timur, Kabupaten Semarang Menggunakan Metode Horizontal to Vertical Spectral Ratio - Mentari, Nur faqhina mentari; Susanti, Dwi Budi (Jurnal Stasiun Geofisika Sleman, 2023)
Research has been conducted on the seismic vulnerability index (Kg) in Kalongan Village, East Ungaran District, Semarang Regency. This study used the Horizontal to Vertical Spectral Ratio (HVSR) method. The purpose of this study is to determine the dominant frequency value (f0), amplification factor (A0), and Kg and analyze the value of the seismic vulnerability index based on data acquisition in Kalongan Village, East Ungaran District, Semarang Regency from June 1 to 4, 2023. Microtremor signals will be read through Geopsy software to obtain f0 and A0 values which will later be used to calculate Kg values in Ms. Excel. From the results of data processing, varying f0 values were obtained, which were between 0.5-11.9 Hz. Similar to f0 values, A0 and Kg values also varied, namely 1.6-3.8 and 0.5-18.8. Based on the contour map of the Kg index, Kalongan Village, East Ungaran District has a low to high vulnerability index.